Picard Sequence and Fixed Point Results on b-Metric Spaces - Marta Demma; Pasquale Vetro (Journal of Function Spaces)
We obtain some fixed point results for single-valued and multivalued mappings in the setting of a b-metric space. These results are generalizations of the analogous ones recently proved by Khojasteh, Abbas, and Costache.